A Correlational Analysis of Social Factors with Obesity among Malay Obese People - Ullah, Saif; Abdul Ghani, Norizan; Ameen Baig, Atif (International Journal of Engineering and Technology, 2018)
This study examines the correlation between social factors and obesity among Malay obese people (age: 20-59 years old) in Terengganu, Malaysia. Comprised of cross-sectional research design, this study has been applied a convenience sampling technique. Clinical Practice Guidelines on Management of Obesity (2004) criteria was adopted < 27.49kg/m2 to measure the body mass index. The number of participants were included in this study n = 150 (male = 80 & females = 70). Data is collected by using close-ended self-administrated questionnaire. SPSS version 21.0 was used for the data analysis. The results reveals that obesity is significantly correlated with feelings (low self-esteem), body image dissatisfaction, eating and dieting frequency (eating habits), frequency of exercise (physical inactivity), physical activity barriers, and media influence. Moreover, obesity has found insignificant with health knowledge, religious knowledge, religious practices and their relation with obesity. It is a pioneer study that has assessed the correlation of social factors and obesity among Malay obese adults in Terengganu, Malaysia. This study reports that majority of the social factors are significantly correlated with obesity. Therefore, interventional programs should be arranged by government based on the social factors in order to decrease the level of obesity in Terengganu, Malaysia.Â Â